Neotropical primary bat cell lines show restricted dengue virus replication. (February 2017) - Moreira-Soto, Andrés; Soto-Garita, Claudio; Corrales-Aguilar, Eugenia
Abstract: Dengue is the most widespread arboviral disease affecting humans. Bats are recognized carriers of emerging viral zoonoses and have been proposed as dengue reservoirs, since RNA/NS1 and/or antiviral antibodies have been detected. Yet, experimental inoculation of Artibeus bats failed to show virus replication. This conflicting results prevent drawing further conclusions of whether bats sustain dengue infection. To test bat cellular permissivity to dengue infection, we established primary bat embryonic cells from diverse organs and tissues of Artibeus jamaicensis, Molossus sinaloae, and Desmodus rotundus . We observed a limited serotype-, organ-, and bat species- specific dengue susceptibility. Only some Molossus -derived primary cells sustained poorly initial Dengue serotype-1 replication, though it was latter absent. To elucidate if Molossus bats may play a role in dengue replication, ecological or in vivo experiments must be performed. Taken together our results show that Dengue did not replicate efficiently in cell lines derived from Neotropical bat species.